THE SIGNIFICANCE OF PEDAGOGY AND SPORT IN PEOPLES LIFE - Mukhametov Akhmad Mukhametovich; Tashpulatov Farhod Alisherovich (International Journal of Innovations in Engineering Research and Technology, 2021)
Human life and health are the greatest social wealth. This raises the issue of a healthy lifestyle for the family, school and other institutions of human development. The health of the nation is also naturally addressed through a healthy lifestyle. Health is a balanced unit of biological, mental, physical condition and labor activity of the human body. Health is happiness for everyone. Its labor productivity is a necessary condition for the development of the country's economic power and the well-being of the people. A conscious and responsible approach to public health, which is a public property, should be the norm of life and morality of society and all its members. In order to maintain and strengthen health, first of all, a person must know the laws of normal functioning, growth, development and reproduction of all tissues and organs of the body.